Designed ankyrin repeat proteins as actin labels of distinct cytoskeletal structures in living cells - Ivanova, Julia; Benk, Amelie S.; Schaefer, Jonas V.; Dreier, Birgit; Hermann, Leon O.; Plückthun, Andreas; Missirlis, Dimitris; Spatz, Joachim P. (ACS nano, 2024)
The orchestrated assembly of actin and actin-binding proteins into cytoskeletal structures coordinates cell morphology changes during migration, cytokinesis, and adaptation to external stimuli. The accurate and unbiased visualization of the diverse actin assemblies within cells is an ongoing challenge. We describe here the identification and use of designed ankyrin repeat proteins (DARPins) as synthetic actin binders. Actin-binding DARPins were identified through ribosome display and validated biochemically. When introduced or expressed inside living cells, fluorescently labeled DARPins accumulated at actin filaments, validated through phalloidin colocalization on fixed cells. Nevertheless, different DARPins displayed different actin labeling patterns: some DARPins labeled efficiently dynamic structures, such as filopodia, lamellipodia, and blebs, while others accumulated primarily in stress fibers. This differential intracellular distribution correlated with DARPin-actin binding kinetics, as measured by fluorescence recovery after photobleaching experiments. Moreover, the rapid arrest of actin dynamics induced by pharmacological treatment led to the fast relocalization of DARPins. Our data support the hypothesis that the localization of actin probes depends on the inherent dynamic movement of the actin cytoskeleton. Compared to the widely used LifeAct probe, one DARPin exhibited enhanced signal-to-background ratio while retaining a similar ability to label stress fibers. In summary, we propose DARPins as promising actin-binding proteins for labeling or manipulation in living cells.
Online veröffentlicht: 15. März 2024
Gesehen am 21.08.2024